Author Correction: Lung endothelial cell antigen cross-presentation to CD8+T cells drives malaria-associated lung injury (Nature Communications, (2019), 10, 1, (4241), 10.1038/s41467-019-12017-8) - Claser, C. (Nature Publishing Group, 2022)
10.1038/s41467-019-13025-4